1995
DOI: 10.1111/j.1439-0388.1995.tb00578.x
|View full text |Cite
|
Sign up to set email alerts
|

BoLA class II polymorphism and immune response to Mycobacterium bovis antigens in vitro

Abstract: Summary In a sample of 47 Holstein‐Friesian calves, experimentally sensitized in vivo with a suspension of killed Mycobacterium bovis the BoLA class‐II polymorphism was analysed at the DQA, DQB, and DRB loci to define its role in the specific immune response. Lymphocyte proliferation under PPD stimulation, phagocytosis of killed M. bovis cells, and the humoral response to PPD antigens, tested by ELISA, were performed in vitro 21 days after sensitization to evaluate the specific immune response. All the animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…The BoLA region has shown association with several diseases in cattle; in particular BoLA DRB alleles have been associated with variation in T-cell responses to M. bovis in Holstein calves (Casati et al, 1995). In our study, no association was observed between the BoLA genotype and reactor, suggesting that genetic selection for BLV resistant animals would not increase the herd susceptibility to TB.…”
Section: Discussioncontrasting
confidence: 55%
“…The BoLA region has shown association with several diseases in cattle; in particular BoLA DRB alleles have been associated with variation in T-cell responses to M. bovis in Holstein calves (Casati et al, 1995). In our study, no association was observed between the BoLA genotype and reactor, suggesting that genetic selection for BLV resistant animals would not increase the herd susceptibility to TB.…”
Section: Discussioncontrasting
confidence: 55%
“…Other biologically plausible potential candidate genes, primarily from the immune system, the interface of hostpathogen interaction, have been suggested. The bovine MHC, or BoLA region, has shown association with several diseases in cattle (Lewin et al 1999) and, in particular, BoLA DRB alleles have been associated with variation in T-cell responses to M. bovis antigens studied in vivo in a population of 47 Holstein calves (Casati et al 1995). Similarly, the bovine orthologue of human DC-specific ICAM-3 grabbing non-integrin C-type lectin (DC-SIGN) gene has recently been identified and functionally characterized (Yamakawa et al 2008).…”
Section: (A) Tb Diagnosis In Cattlementioning
confidence: 99%
“…DQ is more complicated: in about half of the haplotypes that have been tested there are duplicated DQA and DQB genes. It is clear that, in cattle, BoLA class II polymorphism plays a role in observed variability in immune responsiveness (Glass et al, 1991(Glass et al, , 2000Glass andMillar, 1994, 1995;Casati et al, 1995;van Lierop et al, 1995a;Newman et al, 1996;Garcia-Briones et al, 2000;Sitte et al, 2002). There are many alleles for DRB3 (104 alleles with 50 major types) and for DQA (47 alleles and 20 major types) and DQB (49 alleles and 30 major types) (http://www.projects.roslin.ac.uk/bola/) ( Fig.…”
Section: Bola Class IImentioning
confidence: 99%